Predicting postdischarge hospital‐associated venous thromboembolism among medical patients using a validated mortality risk score derived from common biomarkers. Issue 5 (20th May 2020) - Snyder, Lindsey; Stevens, Scott M.; Fazili, Masarret; Wilson, Emily L.; Lloyd, James F.; Horne, Benjamin D.; Bledsoe, Joseph; Woller, Scott C.
Abstract: Background: Discharged medical patients are at risk for venous thromboembolism (VTE). It is difficult to identify which discharged patients would benefit from extended duration thromboprophylaxis. The Intermountain Risk Score is a prediction score derived from discrete components of the complete blood cell count and basic metabolic panel and is highly predictive of 1‐year mortality. We sought to ascertain if the Intermountain Risk Score might also be predictive of 90‐day postdischarge hospital‐associated VTE (HA‐VTE). Methods: We applied the Intermountain Risk Score to 60 064 medical patients who survived 90 days after discharge and report predictiveness for HA‐VTE. Area under the receiver operating curve analyses were performed. We then assessed whether the Intermountain Risk Score improved prediction of 2 existing VTE risk assessment models. Results: The Intermountain Risk Score poorly predicted HA‐VTE (area under the curve = 0.58; 95% confidence interval [CI], 0.56‐0.60). Each clinical risk assessment model was superior to the Intermountain Risk Score (UTAH area under the curve, 0.63; Kucher area under the curve, 0.62; Intermountain Risk Score area under the curve, 0.58; P  < .001 for each comparison). Adding the Intermountain Risk Score to these scores did not substantially improve the performance of either risk assessment model (UTAH + Intermountain Risk Score, 0.65; Kucher + Intermountain Risk Score, 0.64). Conclusion: The Intermountain Risk Score demonstrated poor predictiveness for HA‐VTE when compared to existing risk assessment models. Adding the Intermountain Risk Score to existing risk assessment models did not improve upon either risk assessment model alone to justify the added complexity.